Happiness and Wellness Biopsychosocial and Anthropological Perspectives - Irtelli, Floriana; Gabrielli, Fabio (2023)
This book is a collection of chapters on happiness and well-being. It includes contributions from scientists from all over the world, who present different, multifaceted, dialectically open perspectives and sensitivities regarding happiness. The authors discuss happiness and well-being from biological, biopsychosocial, anthropological, and philosophical points of view.